Observations of bowhead whales along the Northern Chukotka peninsula 2010–2012 with comparisons to 1994–1996 and 2002–2005 - V. Melnikov, Vladimir; Zdor, E. (J. Cetacean Res. Manage., 2023)
This paper contains information on the seasonal distribution of bowhead whales (Balaena mysticetus) in coastal waters of Chukotka (northeast Russia) in 2010–2012. Data from shore-based observation posts provides spatial and temporal information about whale distribution and migration in the coastal zones, as well as information about their relative numbers. The spring migration was observed only from Uelen, Russia (66°N, 149°W), near the northwestern entrance to the Bering Strait, and extended from the end of May through the first half of June. Some year-to-year differences in numbers and migration dynamics were observed. During summer, bowhead whales were sighted in the waters of the northern coast of Chukotka Peninsula in July and August. In 2010–2012, single whales and small groups of up to 4–8 whales were observed in the area for days making non-directed movements. Our observations in 2010–2012 demonstrated that many bowhead whales visited Chukotka coast in the autumn (September) before sea ice formation. From past observations, it appears that the autumn migration begins 2–3 weeks earlier on the northwestern coast of the Chukotka Peninsula than in the (northern) entry of the Bering Strait. The autumn migration of bowhead whales began with ice formation and ended with the complete freezing of the waters. Ice conditions appear to drive high variability in timing of the bowhead autumn migration. The northeastern Chukotka coast is one of the most important feeding areas for the Bering-Chukchi-Beaufort (BCB) bowhead whale population.